Enhanced neuronal differentiation by dynamic piezoelectric stimulation. Issue 1 (7th September 2022) - Pinho, Tiffany S.; Silva, Deolinda; Ribeiro, Jorge Cibrão; Marote, Ana; Lima, Rui; Batista, Salete J.; Melo, Rita; Ribeiro, Clarisse; Cunha, Cristiana B.; Moreira, Irina S.; Lanceros‐Mendez, Senentxu; Salgado, António J.
Abstract: Electroactive smart materials play an important role for tissue regenerative applications. Poly(vinylidene fluoride) (PVDF) is a specific subtype of piezoelectric electroactive material that generates electrical potential upon mechanical stimulation. This work focuses on the application of piezoelectric PVDF films for neural differentiation. Human neural precursor cells (hNPCs) are cultured on piezoelectric poled and non‐poled β‐PVDF films with or without a pre‐coating step of poly‐d ‐lysine and laminin (PDL/L). Subsequently, hNPCs differentiation into the neuronal lineage is assessed (MAP2 + and DCX + ) under static or dynamic (piezoelectric stimulation) culture conditions. The results demonstrate that poled and coated β‐PVDF films induce neuronal differentiation under static culture conditions which is further enhanced with mechanical stimulation. In silico calculations of the electrostatic potential of different domains of laminin, highlight the high polarity of those domains, which shows a clear preference to interact with the varying surface electric field of the piezoelectric material under mechanical stimulation. These interactions might explain the higher neuronal differentiation induced by poled β‐PVDF films pre‐coated with PDL/L under dynamic conditions. Our results suggest that electromechanical stimuli, such as the ones induced by piezoelectric β‐PVDF films, are suitable to promote neuronal differentiation and hold great promise for the development of neuroregenerative therapies.